The mass transport based on convection effects in a passive DMFC under open-circuit conditions - Zuo, Kaiyuan; Yuan, Zhenyu; Cao, Cheng; Hao, Yazhe (International journal of hydrogen energy, 2018)
The study investigates the open-circuit characteristics of a passive direct methanol fuel cell (DMFC) based on temperature-induced convection effects, including the reactants distributions at anode, the non-uniform temperature distribution and the methanol crossover. A two-dimensional, well-thought-out numerical model coupling with mass transfer and momentum transfer is exploited for DMFC to investigate its inner component and temperature distributions under open-circuit condition. In addition, a 4.0 cm2 passive DMFC has been designed and manufactured by the laser-cutting technology for experimental verification. The average methanol crossover flux, methanol diffusion coefficient and crossover current are obtained, which coincide with the simulation data well. The temperature-induced convection simulation results show that the distorted temperature distribution becomes more obvious with higher methanol concentration. Furthermore, the polarization curve, cell temperature and open-circuit voltage (OCV) are measured by varying the methanol concentration to conduct more in-depth research on DMFC performance at open circuit state. The results indicate that the temperature is increased, whereas the OCV is decreased with the increase of methanol concentration, accompanied by the phenomenon of methanol crossover is aggravated. The paper provides the theory basis and the optimal operating parameters for safe start-up of DMFC. •A cell model is built to explore the cell performance under open circuit state.•Temperature-induced convection effects are considered in the model.•Novel experiments are developed to verify the accuracy of developed model.•The direct and indirect influences of various parameters on DMFC are analyzed.